Norm Dynamics in Multilateral Arms Control : Interests, Conflicts, and Justice - Müller, Harald, 1949 May 13- (Book collections on Project MUSE., 2013)
"Efforts to create or maintain rules to contain the risks stemming from an unrestrained multilateral arms race are at the core of a world order based on consensual norms rather than on a pure balance of power. Whereas security cooperation is conventionally considered to be motivated primarily by interest- and security-based factors, studies have shown that all actors use moral arguments and are deeply embedded in the normative patterns surrounding their realm of action. Norm Dynamics in Multilateral Arms Control, based on research conducted by a large PRIF team led by Harald M